cDNA sequencing increases the molecular diagnostic yield in Chediak-Higashi syndrome - Kuptanon, Chulaluk; Morimoto, Marie; Nicoli, Elena-Raluca; Stephen, Joshi; Yarnell, David S.; Dorward, Heidi; Owen, William; Parikh, Suhag; Ozbek, Namik Yasar; Malbora, Baris; Ciccone, Carla; Gunay-Aygun, Meral; et al. (Frontiers in Genetics, 2023)
Introduction: Chediak-Higashi syndrome (CHS) is rare autosomal recessive disorder caused by bi-allelic variants in the Lysosomal Trafficking Regulator (LYST) gene. Diagnosis is established by the detection of pathogenic variants in LYST in combination with clinical evidence of disease. Conventional molecular genetic testing of LYST by genomic DNA (gDNA) Sanger sequencing detects the majority of pathogenic variants, but some remain undetected for several individuals clinically diagnosed with CHS. In this study, cDNA Sanger sequencing was pursued as a complementary method to identify variant alleles that are undetected by gDNA Sanger sequencing and to increase molecular diagnostic yield. Methods: Six unrelated individuals with CHS were clinically evaluated and included in this study. gDNA Sanger sequencing and cDNA Sanger sequencing were performed to identify LYST variants. Results: Ten novel LYST alleles were identified, including eight nonsense or frameshift variants and two in-frame deletions. Six of these were identified by conventional gDNA Sanger sequencing; cDNA Sanger sequencing was required to identify the remaining variant alleles. Conclusions: By utilizing cDNA sequencing as a complementary technique to identify LYST variants, a complete molecular diagnosis was obtained for all six CHS patients. In this small CHS cohort, the molecular diagnostic yield was increased, and canonical splice site variants identified from gDNA Sanger sequencing were validated in CHS. The identification of novel pathogenic LYST alleles will aid in diagnosing patients and these molecular diagnoses will also lead to genetic counseling, access to services and treatments and clinical trials in the future.